The Development of Book Creator Assisted Learning E-Modules in the Curriculum Merdeka on Plants as the Source of Life on Earth at Grade IV Elementary School - Muhammad Subhan; Dian Estu Prasetyo; Aprilia Puspita (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study is motivated by the lack of adequate teaching materials, which leads to students struggling to understand the learning material, feeling bored during lessons, and finding the teaching materials unattractive. Additionally, students tend to have an audio-visual learning style. Therefore, it is necessary to develop teaching materials that can assist students in the learning process, enhancing their understanding of the IPAS (Science, Social Science, and Arts) subject. The aim of this study is to produce a valid, practical, and effective e-module for Book Creator in the Merdeka Curriculum on the topic